Batik Dari Canting Ke Printing: Transformasi Teknik Membatik (1975-1980) - Feren Fatma Fatkhia; Bambang Rakhmanto (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to examine the transformation process of batik-making methods in Buaran District, Pekalongan Village, and its economic impact on batik industry actors during the period 1975–1980. The research employs historical methods, which include heuristic steps, source criticism, interpretation, and historiography. The data used consists of primary sources such as statistical reports, newspapers including Berita Yudha and Harian Fajar, and is supported by oral historical sources. The findings indicate that the batik-making practice, which was originally dominated by the traditional canting method, began to shift gradually to the printing technique in the early 1975s. This shift was driven by the need for time and cost efficiency in production, enabling mass production at lower selling prices. The economic impact of this transition allowed batik printing entrepreneurs to dominate the market, while those who continued to use the canting technique were increasingly marginalized. The study concludes that the shift in batik-making methods between 1975 and 1980 marked the beginning of modern batik industry development in Pekalongan, leading to new market segmentation and consumer preferences for Pekalongan batik. Keywords: Batik Pekalongan, Batik Printing, Batik Tulis.